Carbon nanocoils decorated with a porous NiCo2O4 nanosheet array as a highly efficient electrode for supercapacitors. Issue 27 (2nd July 2021) - Khan, Abdul Sammed; Pan, Lujun; Farid, Amjad; Javid, Muhammad; Huang, Hui; Zhao, Yongpeng
Abstract : Well-organized substrate materials are of considerable significance in the development of energy-efficient pseudocapacitor electrodes. Abstract : Well-organized substrate materials are of considerable significance in the development of energy-efficient pseudocapacitor electrodes. Herein, functionalized three-dimensional (3D) carbon nanocoils on nickel foam (CNCs/NF) have been used as the substrate to grow faradaic nickel cobaltite (NiCo2 O4 ) via a solvothermal method. The arrays of NiCo2 O4 were assembled by interconnected ultrathin nanosheets with random inter-particle pores. The number of electroactive sites increased specifically because of the porous feature of NiCo2 O4 nanosheets and the 3D structure of CNCs/NF. Moreover, the CNCs/NF network aided the electrolyte ions in diffusing deeply within the architecture. The NiCo2 O4 /CNCs/NF composite exhibited an outstanding specific capacitance of 2821 F g −1 at the current density of 1 A g −1, a remarkable rate capability (82.4%) and long cyclic stability (91.7% after 3000 cycles). Such encouraging electrochemical performance was attributed mainly to the synergistic interactions of NiCo2 O4 arrays and CNCs/NF substrate that helped achieve efficient redox reactions, enhanced ion diffusivity and excellent electron conductivity. In summary, this binder-free NiCo2 O4 /CNCs/NF composite electrode paves a way towards the synthesis of highly efficacious electrodes for supercapacitors.